Marine Spatial Planning Scheme evaluation based on the conflict analysis system - A case study in Xiamen, China. (15th April 2022) - Hou, Yuting; Xue, Xiongzhi; Liu, Chao; Xin, Fei; Lin, Yanhong; Wang, Shuo
Abstract: To achieve the ultimate goal of the coordination of the three elements: sea use activities, ecological environment, and marine economy, a Marine Spatial Planning (MSP) scheme requires regular evaluation and adjustments, given that one particular scheme may not take all elements into account. However, concrete evaluation methods were rarely studied, and there are few practical cases. In this study, a conflict analysis system consisting of three matrices was established to quantitatively evaluate the conflicts between the three elements. Combined with the assessment of the current status of certain sea area through the application of ArcGIS functions and tools, the major issues that certain scheme needs to address could be summarized. The conflict analysis system could also be applied to evaluate and compare different adjusted schemes under different scenarios, with the aim to determine one that can better promote coordination. The proposed method was applied in the Marine Functional Zoning (MFZ) of Xiamen, China, a precursor of MSP. The results showed that under the current MFZ scheme, conflicts among different sea use activities and conflicts between sea use activities and ecological environment were caused by the dense and diverse setting of functional zones, some overlaps, and the unsatisfying water quality, biological quality, and biodiversity. Also, the current MFZ scheme is too economically oriented to adequately balance the three elements. Based on the setting of different scenarios and evaluation of different adjusted schemes, the syncretic Scenario 4 can better meet the goal of coordination by avoiding overlaps and reducing the over-dense sea use activities, setting reserved areas and establishing restoration zones, as well as adjusting functional zones with greater economic stimulation to areas with lower pressure, etc. The application prospects and study limitations of the method were discussed in the last part. This study can provide great policy implications for Xiamen's future MFZ revision as well as a workable method for MSP scheme evaluation, adjustment, and development in other regions, which is of great significance and innovation to the sustainable management of coastal and marine areas. Highlights: This study developed a feasible method for the quantitative evaluation of the Marine Spatial Planning Scheme. The conflict analysis system could be used to analyze the various conflicts under a certain Marine Spatial Planning scheme. The case study in Xiamen's Marine Functional Zoning scheme proved the applicability of this method. Policy implications for Xiamen's future scheme revision were provided at last.